STAGES OF DEVELOPMENT OF MONEY: FROM BARTER TO CRYPTOCURRENCY (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article describes the stages of development of money, its evolution from simple barter systems to complex practices of cryptocurrencies. It also highlights the transition to digital assets, highlighting key milestones and important innovations that have shaped the concept of money.